Single Port Transumbilical Laparoscopic Surgery versus Conventional Laparoscopic Surgery for Benign Adnexal Masses: A Retrospective Study of Feasibility and Safety - Wang, Si-Yun (Chin Med J (Engl), 2016)
BACKGROUND: Single port laparoscopic surgery (SPLS) is an innovative approach that is rapidly gaining recognition worldwide. The aim of this study was to determine the feasibility and safety of SPLS compared to conventional laparoscopic surgery for the treatment of benign adnexal masses. METHODS: In total, 99 patients who underwent SPLS for benign adnexal masses between December 2013 and March 2015 were compared to a nonrandomized control group comprising 104 conventional laparoscopic adnexal surgeries that were performed during the same period. We retrospectively analyzed multiple clinical characteristics and operative outcomes of all the patients, including age, body mass index, size and pathological type of ovarian mass, operative time, estimated blood loss (EBL), duration of postoperative hospital stay, etc. RESULTS: No significant difference was observed between the two groups regarding preoperative baseline characteristics. However, the pathological results between the two groups were found to be slightly different. The most common pathological type in the SPLS group was mature cystic teratoma, whereas endometrioma was more commonly seen in the control group. Otherwise, the two groups had comparable surgical outcomes, including the median operation time (51 min vs. 52 min, P = 0.909), the median decreased level of hemoglobin from preoperation to postoperation day 3 (10 g/L vs. 10 g/L, P = 0.795), and the median duration of postoperative hospital stay (3 days vs. 3 days, P = 0.168). In SPLS groups, the median EBL and the anal exsufflation time were significantly less than those of the conventional group (5 ml vs. 10 ml, P < 0.001; 10 h vs. 22 h, P < 0.001). CONCLUSIONS: SPLS is a feasible and safe approach for the treatment of benign adnexal masses. Further study is required to better determine whether SPLS has significant benefits compared to conventional techniques.